2000
DOI: 10.1023/a:1001903221046
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study tests the model presented previously by Breivik et al. (1996), in which the extent of periodontitis, an inflammatory disease, is predicted from the reactivity of the HPA-axis. Briefly, the model implies that elevated plasma levels of corticosterone modulate the immune system by shifting the T-helper balance toward a more Th2 response, which, alternately, increases the sensitivity to periodontitis. To test this model, two genetically distinct types of rats that differ both behaviorally and endocrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our results show significant bone loss induced by bilateral ligature around the first mandibular molars following experimental periodontitis, as described by Klausen [32]. There are Gram-negative bacteria producing lipopolysaccharides and enzymes capable of perturbing the host defense system as well as induction of cytokines involved in the activation of the HPA axis [33]. In our study, there was a highly significant increase in the production of NO, as shown by an increase in total NOS activity in the gingival tissue around the first inferior molars as well as an increase in iNOS mRNA expression.…”
Section: Discussionsupporting
confidence: 62%
“…Our results show significant bone loss induced by bilateral ligature around the first mandibular molars following experimental periodontitis, as described by Klausen [32]. There are Gram-negative bacteria producing lipopolysaccharides and enzymes capable of perturbing the host defense system as well as induction of cytokines involved in the activation of the HPA axis [33]. In our study, there was a highly significant increase in the production of NO, as shown by an increase in total NOS activity in the gingival tissue around the first inferior molars as well as an increase in iNOS mRNA expression.…”
Section: Discussionsupporting
confidence: 62%
“…We have shown previously that CCI rats from all behavioural groups have elevated plasma corticosterone levels, peaking on day three [ 41 ]. It is also known that rats with distinct emotional coping responses (proactive versus reactive) show differences in HPA reactivity and helper T lymphocyte polarisation in response to stressors [ 76 , 77 ]. Elevated glucocorticoids are thought to be anti-inflammatory, shifting the balance of helper T lymphocytes towards Th2 [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breivik et al . [25] demonstrated that periodontal disease susceptibility and progression could be explained, at least in part by brain-neuroendocrine – immune regulatory mechanisms. Genetically determined hypothalamus-pituitary- adrenal axis (HPA) reactivity seems to play a vital role, and a possible feedback is likely to occur from periodontal disease.…”
Section: Discussionmentioning
confidence: 99%